Performance Analysis of Junior High School Natural Sciences Teacher Forum on Professional Development - Suryawati, Evi; Fatmala, Kiki; Arnentis, Arnentis; Deswati, Deswati (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The aim of this study was to describe the performance of Junior High School Natural Sciences Teacher Forum (MGMP members) in Pekanbaru on professional development. This study was performed on November 2016 to April 2017. Fifty members of Junior High School natural sciences teacher forumin Pekanbaru that has been actively participating in teacher forumactivity took part in this study. The data collection instruments used in this study are closed questionnaire and open questionnaire.Closed questionnaire consists of 30 statements that are divided into 4 indicators namely motivation, creativity, self efficacy, and attitude.Open questionnaire consists of 5 questions. Questionnaires have passed the validity test stage through pearson correlation test. Reliability test results obtained Cronbach alpha value of 0.89 (good). Descriptive data analysis show that performance of Junior High School Natural Sciences teacher forummembers in Pekanbaru on professional development gained a mean of 4.07 (good)with details of average motivation 4,02 (good), average creativity 3,90 (good), average self effficacy 4,09 (good) and average attitude 4,29 (very good). Based on this study we can conclude that Junior High School Natural Sciences teacher forum members in Pekanbaru had a good performance on professional development.